Concepts and Foundations of Islamic Education Policy from a Public Policy Perspective - Arfan, Ode Rahman; Suti'ah, Suti'ah; Namakule, Rukiah Oktoviani Saputri (research, training and philanthropy institution Natural Aceh, 2024)
The concept and foundation of education policy, particularly Islamic education policy, are crucial components when viewed from a public policy perspective. This aspect shapes the overall framework and approach adopted by the government or educational institutions in developing and executing policies governing the delivery of Islamic education. Therefore, this study seeks to grasp the fundamentals of the concepts and foundations of educational policy, precisely Islamic education policy. The study utilized the library research method (library study), and the findings explore concepts, foundations, and various other elements relating to Islamic education policy from a public policy standpoint. The concept of Islamic education underscores the incorporation of Islamic values in all facets of life, with its basis grounded in the Quran and Hadith. The public policy perspective aids in analyzing different facets of policies implemented by relevant institutions to attain the objectives of Islamic education, encompassing theories and public opinions, as well as the government's role in formulating, executing, and assessing Islamic education policies. Consequently, a thorough comprehension of the concepts and foundations of Islamic education can be gauged and comprehended meticulously, along with a deeper insight into how Islamic education can be harmonized with public policy to achieve shared objectives, namely fostering a moral, cultured, and prosperous society.